2015
DOI: 10.4315/0362-028x.jfp-14-349
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Resistance Patterns, and Risk Factors for Antimicrobial Resistance in Bacteria from Retail Chicken Meat in Colombia

Abstract: As a step toward implementing the Colombian Integrated Program for Antimicrobial Resistance Surveillance (COIPARS), this study aimed to establish the baseline antimicrobial resistance patterns of Salmonella serovars, Escherichia coli, and Enterococcus spp. isolates in retail poultry meat from independent stores and from a main chain distributor center. MICs of the isolates were determined for antimicrobials used both in humans and animals, using an automated system. Salmonella serovars were isolated from 26% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
26
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 39 publications
(38 reference statements)
5
26
4
2
Order By: Relevance
“…Ceftazidime has shown to be a good antibiotic, with no Salmonella isolates being resistant all isolates. This result is consistent with a previous report (Donado-Godoy et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Ceftazidime has shown to be a good antibiotic, with no Salmonella isolates being resistant all isolates. This result is consistent with a previous report (Donado-Godoy et al, 2015).…”
Section: Discussionsupporting
confidence: 94%
“…The high rate of contamination observed in meat samples (28%) is likely to show a breakdown of hygiene at different steps of food processing as well as a lack of adequate refrigeration. The high prevalence of Salmonella isolates in retail meats obtained in this study was similar to that described in previous studies (Donado‐Godoy et al, ; Katoh et al, ; Takeshi et al, ). The 28% overall prevalence of Salmonella isolates observed in this study is lower than that found in other studies conducted in Spain (35.8%; Dominguez, Gomez, & Zumalacarregui, ) and Portugal (60%; Antunes, Reu, Sousa, Peixe, & Pestana, ), but higher than figures reported from Ireland (2.8%; Jordan et al, ) and Romania (13.2%; Tirziu et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Resistance rates to nitrofurantoin in this study are higher than the ones reported in 265 chicken meat samples (7,9%) in Colombia by Donado-Godoy et al [49]. Higher…”
contrasting
confidence: 74%
“…Increasing antibiotic resistance and the lack of new antibacterial agents have revived 260 interest in old compounds such as nitrofurantoin in clinical [46,47]. Despite the renewed 261 importance of nitrofurantoin and the known role of food animals in resistance 262 dissemination, only a few studies include this antibiotic in antimicrobial resistance 263 screenings [48,49].…”
mentioning
confidence: 99%